2010
DOI: 10.3390/s101109687
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Relative-Story Displacement and Local Inclination Angle Using Multiple Position-Sensitive Detectors

Abstract: We propose a novel sensor system for monitoring the structural health of a building. The system optically measures the relative-story displacement during earthquakes for detecting any deformations of building elements. The sensor unit is composed of three position sensitive detectors (PSDs) and lenses capable of measuring the relative-story displacement precisely, even if the PSD unit was inclined in response to the seismic vibration. For verification, laboratory tests were carried out using an Xθ-stage and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…In 2010, Iwao Matsuya and Akira Nishitan (Matsuya et al 2010;Matsui et al 2012) from Japan formed a system with LED and PSD; when the LED moved with the floor, the lens of the PSD captured images of the LED, then projected the images onto the central part of the photosensitive area, and got the displacement time-history curve. , Zeynep Firat Alemdar (Alemdar et al 2011) measured deformation of a four span girder bridge respectively using displacement sensor and photogrammetric method, and the results showed that these two methods agreed well with the measured results.…”
Section: Earth and Space 2014 © Asce 2015 589mentioning
confidence: 99%
“…In 2010, Iwao Matsuya and Akira Nishitan (Matsuya et al 2010;Matsui et al 2012) from Japan formed a system with LED and PSD; when the LED moved with the floor, the lens of the PSD captured images of the LED, then projected the images onto the central part of the photosensitive area, and got the displacement time-history curve. , Zeynep Firat Alemdar (Alemdar et al 2011) measured deformation of a four span girder bridge respectively using displacement sensor and photogrammetric method, and the results showed that these two methods agreed well with the measured results.…”
Section: Earth and Space 2014 © Asce 2015 589mentioning
confidence: 99%
“…Matsuya et al [21] proposed a sensor system to measure the interstory drift of structures. This system comprises three pairs of position-sensitive detectors (PSDs) and light-emitting diode (LED) arrays.…”
Section: Introductionmentioning
confidence: 99%
“…This system comprises three pairs of position-sensitive detectors (PSDs) and light-emitting diode (LED) arrays. The three LED arrays are fixed on the ceiling, and the three PSDs are installed in one location on the floor to enable each PSD to capture the motion of the corresponding LED array [21]. Measurement of the static deformation prior to the installation and calculation of the entire deformation of the structure due to the partitioning approach is inappropriate.…”
Section: Introductionmentioning
confidence: 99%
“…Another application that integrated PSD was in civil structures engineering for optical recording of the relative-story displacement during earthquakes followed by the remnant deformations measurement of the building structure [10]. The sensor unit was composed of three PSDs and lenses capable of measuring the relative-story displacement successfully.…”
Section: Introductionmentioning
confidence: 99%